2012
DOI: 10.1186/1471-244x-12-44
|View full text |Cite
|
Sign up to set email alerts
|

A multi-site controlled trial of a cognitive skills program for mentally disordered offenders

Abstract: BackgroundThe effectiveness of offending behaviour programs in forensic mental health settings is not well established. Thus this study aimed to evaluate the Reasoning and Rehabilitation Mental Health program (R&R2 MHP) among a mentally disordered offender (MDO) population.MethodsA sample of 121 adult males drawn from 10 forensic mental health sites completed questionnaires at baseline and post-treatment to assess violent attitudes, locus of control, social problem-solving and anger. An informant measure of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…The findings of a second, larger study also supported the feasibility and effectiveness of this program with MDOs in medium and low secure forensic facilities (Rees-Jones, Gudjonsson, & Young, 2012) with a completion rate of 78% and significant treatment effects on completion of the program and at follow-up reported. Finally, a study with MDOs in a high secure hospital obtained a group completion rate of 80% and significant treatment effects at outcome for selfreported violent attitudes, coping processes and social problemsolving, and for staff-rated behavior on units (Yip et al, 2013).…”
Section: Interventions Based On the Risk-need-responsivity (Rnr) Modelsupporting
confidence: 64%
“…The findings of a second, larger study also supported the feasibility and effectiveness of this program with MDOs in medium and low secure forensic facilities (Rees-Jones, Gudjonsson, & Young, 2012) with a completion rate of 78% and significant treatment effects on completion of the program and at follow-up reported. Finally, a study with MDOs in a high secure hospital obtained a group completion rate of 80% and significant treatment effects at outcome for selfreported violent attitudes, coping processes and social problemsolving, and for staff-rated behavior on units (Yip et al, 2013).…”
Section: Interventions Based On the Risk-need-responsivity (Rnr) Modelsupporting
confidence: 64%
“…In their multi-site controlled trial using the R&R2MHP, Rees-Jones et al[11] found that 52 out of 67 (78%) of participants completed the programme ( i.e ., completing 80% or more of the sessions). C-Y Yip et al[12] found a completion rate of 80% in a maximum secure unit setting.…”
Section: Introductionmentioning
confidence: 99%
“…No other predictors of non-compliance were examined in this study. Rees-Jones et al[11] found that there were no significant differences between the completers and non-completers in age, previous convictions, previous admissions, and motivation to engage in treatment. The only difference was that non-completers had significantly better problem-solving skills at baseline than the completers (Cohen’s d = -0.65, medium effect size), which seems counter-intuitive.…”
Section: Introductionmentioning
confidence: 99%
“…Effective treatments also need to be developed and the present findings suggest one should focus on modifying violent cognitions using cognitive behavioural therapy programmes such as R&R2 (Rees-Jones et al, 2012;Cin-Ying Yip, et al 2013;Young et al, 2013).…”
Section: Multiple Regressionmentioning
confidence: 99%
“…The MVQ was initially validated using a 'normal' student adolescent population and the two constructs had adequate internal consistency (Machismo: α = 0.91, Acceptance: α = 0.74; Walker, 2005). It has been used successfully to predict the involvement in violent films and computer games among students , predict violence in a forensic in-patient population (Dutheil, 2010;Warnock-Parkes et al, 2008), is significantly correlated with conduct disorder and selfreported offending among young institutionalised offenders (Young et al, 2011), and has been used to determine treatment outcome in forensic inpatient populations (Cin-Ying Yip et al 2013;Rees-Jones et al, 2012;Young et al, 2013). The three treatment outcome studies, all conducted among mentally disordered offenders in secure establishments, showed that violent attitudes were reduced following completion of cognitive skills programmes, which included empathy training.…”
Section: --------Figure 1---------mentioning
confidence: 99%